1982
DOI: 10.1248/bpb1978.5.295
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of flunarizine against cerebral hypoxia-anoxia in mice and rats.

Abstract: The protective effect of flunarizine against cerebral hypoxia-anoxia was investigated with various experimental models in mice and rats. The effect of flunarizine was compared with those of cinnarizine, verapamil and pentobarbital. The oral treatment of animals with flunarizine resulted in a consistent and long-lasting-protection against cerebral hypoxia-anoxia in all the models examined: Cytotoxic anoxia by KCN injection, hypercapnic anoxia induced by stopping artificial respiration, hypobaric hypoxia and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…9 Another calcium entry blocker, flunarizine, has been reported to be a potent cerebral vasodilator," to dramatically improve CBF after complete cerebral ischemia in dogs maintained on cardiopulmonary bypass, 12 and to protect the brain of mice and rats against cerebral hypoxia-anoxia. 13 We therefore studied the effects of flunarizine on CBF, cerebral metabolism of oxygen (CMRO 2 ), and neurologic recovery in an established intact canine model of complete cerebral ischemia and compared the results to those obtained from untreated groups 4 -14 and from pre-treated…”
mentioning
confidence: 99%
“…9 Another calcium entry blocker, flunarizine, has been reported to be a potent cerebral vasodilator," to dramatically improve CBF after complete cerebral ischemia in dogs maintained on cardiopulmonary bypass, 12 and to protect the brain of mice and rats against cerebral hypoxia-anoxia. 13 We therefore studied the effects of flunarizine on CBF, cerebral metabolism of oxygen (CMRO 2 ), and neurologic recovery in an established intact canine model of complete cerebral ischemia and compared the results to those obtained from untreated groups 4 -14 and from pre-treated…”
mentioning
confidence: 99%
“…These effective doses of KMK are not consi dered unusual because other drugs with a protective ac tion against ischemic disorders also need to be given in high doses (e.g., the effective dose of flunarizine for KCN induced death is 120 times higher than the normal clinical dose (16), and the dose of vinpocetine for ischemia is 80 times higher (13)). The protective effects of flunarizine, a Ca" antagonist, against cerebral hypoxia-anoxia in mice and rats (16) and against ischemic injury in gerbils (20) have been reported previously. In the present experiments, flunarizine also showed protective effects against cerebral ischemia, hypoxia and anoxia.…”
Section: Discussionmentioning
confidence: 99%
“…0 1 hypoxia-anoxia 22 and improve postischemic hypoperfusion. 23 Nimodipine prevented postischemic impaired cerebral reperfusion, and promoted functional recovery after cerebral ischemia.…”
Section: Controlmentioning
confidence: 99%
“…23 Nimodipine prevented postischemic impaired cerebral reperfusion, and promoted functional recovery after cerebral ischemia. 24 -M While the mechanism of the protective effect of calcium entry blocker against cerebral ischemia is attributed to a cerebral vasodilat-^ ^| ing action, 22 " 25 some authors suggest the involvement of some other unknown mechanism 22 or protection from mitochondrial calcium accumulation. 23 Hossmann et al M observed that postischemic accumulation of calcium in the brain tissue could not be prevented by the calcium antagonist flunarizine.…”
Section: Controlmentioning
confidence: 99%